Comparative autohydrolysis study of two mixtures of forest and marginal land resources for co-production of biofuels and value-added compounds - Pontes, Rita (2018)
This work was focused on evaluating two mixtures of lignocellulosic feedstock, forest and marginal land resources, in order to co-produce solid biofuel, oligosaccharides, and glucose under a biorefinery concept. The selection of renewable bio-mixtures was based on different criteria, namely, territorial distribution, fire risk during summer months and total sugar content. The two mixtures were submitted to autohydrolysis pretreatment under non-isothermal conditions (in the range of 190°C - 240°C corresponding to severity of 3.714.82). Both mixtures were compared in terms of fractionation (cellulose and lignin recoveries and hemicellulose solubilization), analyzed for thermal properties (high heating values) and for enzymatic susceptibility of cellulose. The highest xylan recoveries (62 and 69%), as xylose and xylooligosaccharides, were achieved for both mixtures in the liquid phase at 206°C. Autohydrolysis pretreatment increased the high heating values of the two mixtures presenting an alternative use of solid fraction as solid biofuel. Moreover, enzymatic susceptibility of these pretreated mixtures was also improved from 45 to 90% of glucose yield by increasing pretreatment severity. This comparative study of autohydrolysis showed a suitable process for the valorization of both mixtures within a biorefinery concept.